Situação de mídia: os meios de comunicação na filmografia de Pedro Almodóvar - Carlos, Gustavo Colares Melo (2010)
Presenting as theme the filmography of 17 commercials full-length films of Spanish director Pedro Almodóvar, from “Pepi, Luci, Bom y otras chicas del montón”, 1980, to “Abraços partidos”, 2009, this paper intends to investigate how film sequences here nominated media situations assist the filmmaker in the narrative development of his productions. When identifying the frequency that the filmmaker approaches the mass media universe during his cinematographic trajectory, the intention is to understand in which way these media situations can interfere in the characters construction and generation of events in the films, as a narrative device. For this, the present research related theoretical studies on the media and the social communication to Almodovar's filmography, as the occurrence of fait divers in the press, analyzed by Barthes (1977), and Luhmann's systems theory (2005).